An ultrastructural study of the Sertoli cell in the water buffalo Bubalus bubalis - Kurohmaru, M.; Yamashiro, S.; Azmi, T.I.; Basrur, P.K. (Wiley, 1992)
The ultrastructure of Sertoli cell in the water buffalo Bubalus bubalis was observed in a transmission electron microscope. The nucleus had homogeneous nucleoplasm, scarce heterochro‐matin and multivesicular nuclear body (MNB). The MNB was composed of numerous vesicles and ribosome‐like dense structures. The vesicles varied in size and number and contained a sparse and flocculent substance. In the indentation of the nucleus, aggregates of ribosomes were frequently observed. In the apical and middle region of the cell, long mitochondria and microtubules were distributed parallel to the long axis of the cell. Non‐laminated smooth ER and some ribosomes were also recognizable throughout this region. In the basal region, widely‐distributed laminated smooth ER was characteristic. Microfilament bundles at ectoplasmic specialization were irregularly arranged. Frequently‐emerged nodular processes occasionally separated from basal lamina and formed round structures within Sertoli cytoplasm. Although these characteristics of buffalo Sertoli cell were very similar to those of the bovine studied, the aggregate of ribosomes was more developed in the buffalo. Copyright